2019
DOI: 10.5902/2316980x36338
|View full text |Cite
|
Sign up to set email alerts
|

Raízes finas em árvores jovens de <em>Eucalyptus dunnii</em> Maiden

Abstract: As raízes finas proporcionam o cultivo do eucalipto nas mais diversas condições edáficas, contribuindo à ciclagem de nutrientes e melhoria da fertilidade do solo. O presente estudo teve o objetivo de caracterizar a produção de biomassa e distribuição das raízes finas (≤ 2 mm) em árvores jovens de Eucalyptus dunnii Maiden, cultivadas no bioma Pampa, Rio Grande do Sul. Aos 16 meses após o plantio foram coletados nove monólitos, divididos em 0 a 5, 5 a 10, 10 a 15 e 15 a 20 cm de profundidade do solo. A produção … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
(27 reference statements)
0
3
1
Order By: Relevance
“…For line position to the highest value was 600 kg ha -1 at T2 and 325 kg ha -1 at T5. Dick et al (2019) found an organic matter of the soil of 1.4% for the respective layer, while for the present study it was only 0.2%. This can explain the lower production of fine roots.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…For line position to the highest value was 600 kg ha -1 at T2 and 325 kg ha -1 at T5. Dick et al (2019) found an organic matter of the soil of 1.4% for the respective layer, while for the present study it was only 0.2%. This can explain the lower production of fine roots.…”
Section: Discussioncontrasting
confidence: 71%
“…Although the highest density of fine roots g / dm³ is observed in T2, the average for depth 0 -20 cm in all positions and treatments was 0.16 g / dm³ . Assessing the depth 0 -20 cm in Eucalyptus dunnii stands at 16 months, Dick et al (2019) found an average fine root density of 0.36 g / dm³ . Part of the results are due to age of the stand.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The characterization of action research varies from one author to another. However, there is a set of common characteristics (Dick, 2000):…”
Section: Methodsmentioning
confidence: 99%